Identification of peptide sequence to block dengue virus transmission into cells via In Silico and In Vitro Assays / Aathe Cangaree Arumugam - Aathe Cangaree , Arumugam (2020)
Dengue virus (DV) infection has become main public wellbeing concerns, affecting approximately 390 million people worldwide. This fact was reported by the World Health Organization. Yet, there is no commercial antiviral treatment for DV infection. Therefore, the development of potent and non-toxic anti-DV, as a complement for the existing treatment strategies, are urgently needed. Herein, we investigate a series of low molecular weight peptides inhibitors by aiming the cellular entry process as the promising approach to block DV infection. The peptides were designed based on previously reported peptide sequence, DN58opt (TWWCFYFCRRHHPFWFFYRHN), to identify minimal effective inhibitory sequence via molecular docking and molecular dynamics simulation studies. The in silico designed peptides were synthesized using conventional FMOC solid-phase peptide synthesis chemistry, purified by RP-HPLC, and characterized using LCMS. Later, they were screened for their antiviral activity. One of the peptides, AC 001, showed the best inhibitory activity towards DV2 with inhibition percentage of 40.34% ± 5.9%. This observation correlates well with the molecular mechanics-Poisson–Boltzmann surface area (MM-PBSA) analysis – AC 001 showed the most favourable binding affinity (-33.51 ± 5.11 kcal/mol) through 60ns simulations. Trough pairwise residue decomposition analysis, it was found that the key residues involved in the binding were mainly, Glu13, Arg350, Leu351, and Ser16 for the protein and F3, Y4, Y5, and R7 for AC 001. Hence, this work identifies the minimal peptide sequence required to inhibit DV replication and explains the behaviour of AC 001 towards DV2.